Accounting educators' perceptions on teaching ethics in the accounting curriculum - Win, Yin Yin; Ismail, Suhaiza; Abdul Hamid, Fatima (2011)
The purpose of this study is to investigate ethics education in the accounting curricula of Malaysian public universities based on the perception of the educators. The study explored preparedness of educators in teaching ethics, preferred methods of ethics instruction, and educators’ perceptions of importance of ethics integration. Consistent with prior Western studies, this study finds that accounting educators agree on the importance of ethics education to satisfy the profession’s needs. However, different opinions exist among educators on the adequacy of ethics coverage. The educators’ perceptions on integrating ethics education in accounting curriculum support the Utilitarianism approach.